Pemikiran Pendidikan Islam Perspektif KH. Ahmad Dahlan (1869-1923 M) dan KH. Hasyim Asy'ari 1871-1947) M): Study Komparatif dalam Konsep Pembaruan Pendidikan Islam di Indonesia - Ni'mah, Zetty Azizatun (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2014)
This article aims at analyzing and comparing thoughts of KH. Ahmad Dahlan andKH. Hasyim Asyari on the reform of Islamic education as well as their correlationwith the current education system. This issue will be examined by using libraryresearch. The analysis uses historical, sociological and anthropological approaches.The results of the research suggest that the concept of Islamic education reformof KH. Ahmad Dahlan and KH. Hasyim Asyâ€™ari are similar, namely: the aim ofIslamic education is to form insan kÄmil, educational materials in Islam is anintegral material between religion and science, educational methods were varied,and the development of educational institutions in the form of Islamic Senior HighSchool. The difference in the concept of Islamic education reform between the twois the direction and orientation of education. For KH. Ahmad Dahlan, the aimof Islamic education leads to increas economic and political life, and to enhancesocial welfare through modernism in education. For KH. Hasyim Ashâ€™ari, the goalof education is to improve the moral quality of the people through maintainingtraditionalist Islamic culture, by using classical books as an important materialto be studied in developing religious knowledge.